Making Sense of 1917: Towards a Global History of the Russian Revolution. Issue 3 (23rd October 2017) - Rendle, Matthew
Abstract : It is clear that the global impact of the Russian Revolution over the last century has been immense. What is less clear, however, is the global impact on the revolution. Historians have appreciated that contemporaries made immediate comparisons with previous revolutions, especially the French Revolution and the Paris Commune, but considerations of broader global influences on the revolution have been rare. This article explores how historians can study these global influences, exploring the circulation of ideas and their influence on people and policies. Whilst not denying the continuing primacy of traditional "internal" factors in explaining the nature and process of the revolution, the article argues that globalizing 1917, as contemporaries did, helps historians to better understand the widespread belief in progress that fueled developments as people sought to create a new country, and to appreciate how people tried to make sense of the tumultuous events of revolution.